A cloud model-based approach for risk analysis of excavation system. (March 2023) - Shen, Shui-Long; Lin, Song-Shun; Zhou, Annan
Highlights: A cloud model-based approach is proposed. Multi-source information related to excavation system are considered. A novel way is provided to perceive the risk status of excavation system. A case study for risk status perception for excavation system is illustrated. It presents guideline for risk analysis and management of excavation engineering. Abstract: Excavation construction in urban dense areas is regarded as a high-risk activity since there are various aspects involved and risk usually occurs in local part of excavation. This paper presents a cloud model-based approach to evaluate risk status of excavation. Multi-source information related to excavation can be coped with the developed approach. Approach development involves three phases: multi-sources information collection, construction of the benchmark cloud model (BCM) and identified cloud model (ICM), and risk level determination. Two-stage weight determination is developed to aggregate multi-sources information. An excavation project in Zhuhai is adopted to verify the performance of developed approach. Excavation was divided into subsystems according to monitoring plan of factors and risk status of subsystems is estimated based on the similar membership degree calculation between BCM and ICM. Results were found to be consistent with field situation. The sensitivity factors towards estimated risk status results were identified through correlation analysis. This proposed approach provides a novel way of perceiving the risk status of excavation and guidelines for risk management. Graphical Abstract: Image, graphical abstract